THE IMPACT OF SOCIAL MEDIA ON STUDENTS AT DONG NAI MEDICAL COLLEGE IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: The objective of this study is to identify factors influencing social media use behaviors among students at Dong Nai Medical College.Subjects and research methods: Students studying at Dong Nai Medical College.Conclusion: Social media has become an integral component of students’ daily lives and exerts both positive and negative effects. On the positive side, students clearly recognize its role in facilitating communication, entertainment, and stress reduction. Conversely, approximately 40–45% of students report occasionally experiencing emotional pressure, time constraints, and difficulties in self-regulation associated with social media use. Students also identify usage behaviors as the most influential factor, encompassing awareness, attitudes, and age-related psychological characteristics. In addition, external factors, such as technological resources and living conditions, play a significant role.
Keywords: Behaviors, social media, student, Dong Nai Medical College